The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4269/ajtmh.2011.10-0589
|View full text |Cite
|
Sign up to set email alerts
|

Placental Malaria and Mother-to-Child Transmission of Human Immunodeficiency Virus-1 in Rural Rwanda

Abstract: We conducted a nested case-control study of placental malaria (PM) and mother-to-child transmission (MTCT) of human immunodeficiency virus-1 (HIV-1) within a prospective cohort of 627 mother-infant pairs followed from October 1989 until April 1994 in rural Rwanda. Sixty stored placentas were examined for PM and other placental pathology, comparing 20 HIV-infected mother-infant (perinatal transmitter) pairs, 20 HIV-uninfected pairs, and 20 HIV-infected mothers who did not transmit to their infant perinatally. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
(43 reference statements)
0
9
1
Order By: Relevance
“…Our finding of a statistically significant positive association between MIP and MTCT is corroborated by findings of a twofold higher risk of HIV MTCT among HIV‐positive mothers with MIP in the Rakai District of Uganda and the recently reported sixfold elevated odds of early HIV MTCT for infants of Rwandan HIV‐positive women with MIP . Our results are further supported by the finding of a higher risk of MTCT among HIV‐positive pregnant women with high‐density placental malaria in western Kenya and the recent finding of a MIP associated increased risk of HIV MTCT by Msamanga et al .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding of a statistically significant positive association between MIP and MTCT is corroborated by findings of a twofold higher risk of HIV MTCT among HIV‐positive mothers with MIP in the Rakai District of Uganda and the recently reported sixfold elevated odds of early HIV MTCT for infants of Rwandan HIV‐positive women with MIP . Our results are further supported by the finding of a higher risk of MTCT among HIV‐positive pregnant women with high‐density placental malaria in western Kenya and the recent finding of a MIP associated increased risk of HIV MTCT by Msamanga et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, there is little research on the potential contribution of coincident infections, such as malaria in pregnancy (MIP), to early HIV MTCT among HIV-exposed infants of HIV-infected women in SSA; when available, results have been inconclusive [6][7][8][10][11][12][13][14][15][16]. In a short-term prospective study of infants born to 277 HIV-positive Kenyan women and 372 HIV-negative hospital-based controls, Inion et al found no association between placental malaria and in utero or peripartal transmission of HIV-1 by 6 weeks [13].…”
Section: Introductionmentioning
confidence: 99%
“…Early work suggested that the combination of PM and maternal HIV was associated with increased infant mortality relative to HIV infection alone but did not specifically examine the HIV status of the offspring . PM as a specific risk factor for mother to child transmission (MTCT) of HIV, after adjustment for HIV viral load, has subsequently been confirmed . Not all studies, however, support this conclusion.…”
Section: Maternal Malaria Predicts An Increased Risk Of Nonmalarial Amentioning
confidence: 99%
“…Antibiotic therapy of infections such as typhoid fever and listeriosis might have to be extended beyond the 2 weeks recommended for non-pregnant individuals especially if infection occurs during the first trimester. 22,23 …”
Section: Looking Aheadmentioning
confidence: 99%